Potential of Fruit and Vegetable Waste as Eco-enzyme Fertilizer for Plants - MTh Sri Budiastuti; MMA Retno Rosariastuti; Thanya Fadlilla (Postgraduate, University of Mataram, 2023)
This study aims to determine the source of eco-enzyme raw materials and the most appropriate dilution volume to produce quality eco-enzyme fertilizer for plant growth. 1 (sugar): 3 (fruit and vegetable waste): 10 (water). The resulting eco-enzyme liquid is processed into fertilizer through the dilution process. Eco-enzyme fertilizers from each raw material source contain different organic N, P, K, and C nutrients. Besides that, some enzymes are beneficial to plants. This research is experimental in the laboratory. The experimental design was factorial design using a completely randomized design as the based design with the treatment of various sources of raw material for eco-enzyme E1 (fruit waste), E2 (vegetable waste), and E3 (fruit and vegetable waste). The parameters observed are N, P, K, and C Organic. The results showed that in terms of the quality of eco-enzyme fertilizers, the best order of eco-enzyme fertilizers was eco-enzyme fertilizer from vegetable waste (E2), eco-enzyme fertilizer from fruit and vegetable waste (E3), and eco-enzyme fertilizer from fruit waste (E1). Based on the NPK content in eco-enzyme fertilizer, eco-enzyme fertilizer is still below the quality standard for liquid organic fertilizer but the enzymes contained in eco-enzymes can also spur growth in plants.